A reducing system of the superoxide sensor SoxR in Escherichia coli - Koo, Mi-Sun (Oxford University Press, 2003)
The soxRS regulon functions in protecting Escherichia coli cells against superoxide and nitric oxide. When SoxR is activated by oxidation of its [2Fe–2S] cluster, it increases the synthesis of SoxS, which then activates its target gene expression. How the oxidized SoxR returns to and is maintained in its reduced state has been under question. To identity genes that constitute the SoxR-reducing system, we screened an E.coli mutant library carrying a chromosomal soxSp::lacZ fusion, for constitutive mutants. Mutations mapped to two loci: the rsxABCDGE operon (named for reducer of SoxR) that is highly homologous to the rnfABCDGE operon in Rhodobacter capsulatus involved in transferring electrons to nitrogenase, and the rseC gene in the rpoE–rseABC operon. In-frame deletion of each open reading frame in the rsxABCDGE operon produced a similar constitutive phenotype. The double mutation of rsx and rseC suggested that rsxABCDGE and rseC gene products act together in the same pathway in reducing SoxR. Electron paramagnetic resonance analysis of SoxR and measurement of re-reduction kinetics support the proposal that rsx and rseC gene products constitute a reducing system for SoxR.